Eksistensi beasiswa teladan: Pengaruhnya Terhadap Perekonomian dan Prestasi Studi Mahasiswa - Permadi, Bagas Bintang (Maliki Interdisciplinary Journal, 2026)
Scholarships are an important component for some students who wish to continue their education to higher education. The Teladan Scholarship is a tuition fee financing program from the UIN Malang Institution for prospective students who have achievements in academic and non-academic fields. This study aims to analyze the existence of the economy, fluctuations in achievements and studies of UIN Malang students. This study uses a descriptive qualitative method with the results of observations and interviews from respondents who received the Teladan Scholarship UIN Malang 2025/2026. The results of this study indicate that the Teladan Scholarship is effective in improving the economic needs and academic achievements of students both academically and non-academically, but it cannot be denied that this Scholarship has a limited quota and gives rise to a consumptive nature of the students themselves. Therefore, this scholarship plays a strategic role in helping students economy and academic achievements, by optimizing it in the form of concrete data collection, and conducting continuous evaluations so that the objectives and benefits of the scholarship can be realized well and more evenly